Mampukah Sistem E-Laporan Meningkatkan Efektivitas Pengawasan Kegiatan Penyuluhan di Kabupaten Sleman? - Pande Putu Dhika Yoni Kartika; Dwiningtyas Padmaningrum; Bekti Wahyu Utami (AGRITEXTS: Journal of Agricultural Extension, 2024)
The extension e-report system is an online system used by field agricultural extension workers in Sleman Regency to report their extension activities every month online through the www.penyuluhan.jogjaprov.go.id website. This study aims to examine the influence of system quality on system use, inspect the influence of system quality on user satisfaction, test the influence of information quality on system use and user satisfaction, the influence of system use on user satisfaction, the influence of user satisfaction on system use, the influence of system use on individual impact and the influence of satisfaction users to individual impacts using the DeLone & McLean IS Success Model. The quantitative research method is carried out in all Agricultural Food and Fisheries Extension Center (BP4) in Sleman Regency, Yogyakarta Province, with 90 respondents in field agricultural extension taken using the census technique—the research analysis using SEM PLS with SmartPLS 3.0 software. The results of the study show that (1) the quality of the system does not affect the use of the system. (2) The system’s quality does not affect user satisfaction. (3) The quality of information affects the use of the system. (4) The quality of information affects user satisfaction. (5a) The use of the system affects user satisfaction. (5b) User satisfaction affects the use of the system. (6) Using the system affects the impact of the Individual. (7) User satisfaction affects individual impact. The research results are expected to provide input for improving this e-report system to make the supervision process more effective.